LINKAGES SHARIAH GOVERNANCE AND ISLAMIC BANKS PERFORMANCE: EVIDENCE FROM GULF COOPERATION COUNCIL (GCC) COUNTRIES - Prasojo; Muhfiatun; Listiyorini, Inon; Utami, Ristianawati Dwi (Media Riset Akuntansi, Auditing & Informasi, 2024)
The shariah governance system is crucial for Islamic banks (IB) because of the unique structure that is different from conventional banks. Good governance has an impact on stable performance. The shariah supervisory board (SSB) presence will convince stakeholders that IBs are running their business according to shariah principles. The focus of this research is the results of empirical studies in GCC countries. The research data was obtained from the bankscope database and manual collective from 2010-2018. This study uses a panel data model with a random effect method. Empirical results show that SSB size has a negative correlation with performance. SSB expertise and board size have a positive correlation with performance. Furthermore, SSB with doctoral qualifications and independent boards are not correlated with performance